Implementasi Kegiatan Ekstrakurikuler Keagamaan Dalam Penanaman Pengetahuan Agama Siswa MAN 2 Langkat - Tri Widya Wati, Zaifatur Ridha, Nurmisda Ramayani (Khazanah : Journal of Islamic Studies, 2022)
Aim study this is for knowing Implementation of Religious Extracurricular Activities in Inculcating Religious Knowledge of Man 2 Langkat Students . Method study this is The type of this research is qualitative research. The data sources for this research were school principals, teachers, religious extracurricular coaches and religious extracurricular participants. Data collection in qualitative research was obtained using observation, interviews, methods of literature and documentation. The results of the research show Implementation activity extracurricular religion in MAN 2 Langkat this done outside of school hours that is when go home school . As for Form activity Extracurricular religion at MAN 2 Langkat are KKD and LPTQ. In its implementation, KKD is held once a week on Thursday after school starting at 15:00 – 17:00 WIB. Implementation of LPTQ at MAN 2 Langkat is carried out every Friday at 14:00 – 17:00 where in its implementation LPTQ is divided into 5 areas, namely, recitation, tahfiz, Kaligradi, Syahril and Fahmil Qur'an. The cultivation of religious knowledge that was implanted in MAN 2 Langkat was instilled through religious activities held at this madrasa. Starting from the activities of reading the Koran in the morning, congregational midday prayers, reciting the Yasin Tahtim and the overall prayer tahlil which are held every Friday in the field. Besides that's a teacher too very role in give understanding religious student through the PAI learning process . The Implementation of Religious Extracurricular Activities in Inculcating Religious Knowledge for MAN 2 Langkat Students is carried out well where the values stated in each activity are internalized in the students' personalities and then emerge characters that can be embedded in their daily lives. Another thing that distinguishes students who take religious extracurriculars is the comparison between students who take religious extracurriculars and those who don't. It is very much different from the attitude, behavior, manners and politeness which is very good because it has also been accompanied by activities that are religious in nature which involve things that are prohibited. especially adab, in practicing religious teachings more than others, it can be seen from the prayer times, students who take part in these religious activities are on time compared to others often missed.